Model Pengelolaan Amenitas Berkelanjutan pada Daya Tarik Wisata Pantai Tanjung Karang Kabupaten Donggala - Muh. Rais Rizal Maspe; Nina Mistriani (LPPM Institut Pendidikan Nusantara Global, 2026)
The potential tourism attractions of Donggala Regency are important to develop into sustainable tourism attractions because tourism plays a strategic role in supporting regional economic growth and improving community welfare. One of the most promising destinations in this area is Tanjung Karang, which has natural coastal beauty and cultural potential that can attract both domestic and international tourists. However, the main problem raised in this research is how to improve the amenities of Tanjung Karang to enhance tourist comfort when visiting Banawa District, Donggala Regency. Inadequate supporting facilities, limited infrastructure, and insufficient tourism services are still obstacles that reduce visitor satisfaction and length of stay. Research data collection was conducted through observation and interviews using qualitative research methodology to obtain an in-depth understanding of existing conditions, stakeholder perceptions, and challenges faced in tourism development. The findings indicate that to support sustainability, infrastructure such as access roads, accommodation facilities, sanitation, and public amenities must be added and improved. In addition, tourism marketing must be developed through digital promotion, branding strategies, and collaboration with tourism stakeholders. These efforts are expected to attract more tourists to Tanjung Karang, increase visitor satisfaction, create employment opportunities for local communities, and boost the growth of the tourism industry in Donggala Regency in a sustainable and inclusive manner.